Prince Valentino - Bos, Burny, 1944-; De Beer, Hans (New York : North-South Books, 1990)
Valentino, a spoiled little frog, learns that he isn't really a prince but realizes that he has met a beautiful princess.
Translation of: Valentino Frosch und das himbeerrote Cabrio.
Booklist
School Library Journal
2.7
K-3
Keywords: Storks -- Fiction; Friendship -- Fiction; Frogs -- Fiction; Storks -- Fiction; Friendship -- Fiction; Frogs -- Fiction